Oxygen Reduction Reaction Using N4-Metallomacrocyclic Catalysts: Fundamentals on Rational Catalyst Design - Zagal-Moya, J; Zagal-Moya, J (World Scientific Publishing Co. Pte Ltd, 2012)
In this review, we describe and discuss the developments in the use of metalloporphyrins and metallophthalocyanines as catalysts for oxygen reduction in aqueous electrolytes. The main goal of most researchers in this field has been to design catalysts which can achieve facile reduction of oxygen by the four-electron transfer pathway at the lowest overpotential possible. With this in mind, the primary objective of this review was to bring to light the research frontiers uncovering important milestones towards the synthesis and design of promising N4-metallomacrocyclic catalysts which accomplish the four-electron reduction of oxygen, and, based on literature, to draw attention to the fundamental requirements for synthesis of improved catalysts operating at low overpotentials. Our emphasis was not to make parallel comparisons between individual classes of N4-metallomacrocyclic complexes with respect to their activity, but rather to focus on the commonalities of the fundamental properties that govern their reactivities and how these may be aptly manipulated to develop better catalysts. Therefore, besides discussion of the progress attained with regard to synthesis and design of catalysts with high selectivity towards four-electron reduction of O2, a major part of the review highlights quantitative structure-activity relationships (QSAR) which govern the activity and stability of these complexes, which when well understood, refined and carefully implemented should constitute a fundamental gateway for rational design of better catalysts. Copyright © 2012 World Scientific Publishing Company.